The Impact of the Covid-19 Pandemic on the Social Development of Elementary School Children - Rindi Rendiyawati; Triana Lestari (Universitas Muhammadiyah Enrekang, 2021)
At this time the government provided a policy to implement online schools where children learn independently and the role of teachers is completely replaced by parents, this study aims to raise the problem of social development in the pandemic era where learning is carried out at home without direct interaction with teachers and friends. The impact of social development for elementary school children in this online era is very diverse, we can see because of the effects of the COVID-19 virus, the purpose of this study is to determine the social impact of online learning for elementary school children, the type of research used is literature. from various sources and use forms to parents who supervise the social development of children during the pandemic.